Oral anticoagulant treatment in patients with atrial fibrillation early after valvular intervention: a nationwide cohort study. (3rd October 2022) - Christersson, C; Skogseid, E L; Westerbergh, J; Held, C; Batra, G
Abstract: Background: Treatment with non-vitamin K oral anticoagulants (NOAC) is the first option for primary prevention of ischaemic stroke in patients with atrial fibrillation (AF). However, there is still an evidence gap regarding efficacy and safety of NOAC in patients with AF and severe valvular heart disease undergoing valvular intervention. Purpose: The aim was to evaluate the efficacy and safety of NOAC or no oral anticoagulant (OAC) treatment versus warfarin during the first 3 months after valvular intervention. Methods: We used data from the National Quality Register SWEDEHEART and included all patients with AF discharged after surgical valvular intervention with bioprosthesis or valvuloplasty, or transcatheter aortic valve implantation (TAVI) between 2010 and 2016. Outcomes, including the composite of cardiovascular (CV) events (CV death, ischaemic stroke or systemic embolism), major bleeding, and relevant comorbidities and OAC treatment at discharge were collected from the National Patient Register, the Swedish Prescribed Drug Register, and the National Cause of Death Register. The association between exposure (warfarin, NOAC or no OAC) and occurrence of composite CV events and major bleeding was explored using a time-dependent adjusted Cox regression analysis. Results: In total, 4730 patients with AF and valvular intervention were included. The cohort had a mean age of 75 years, 35.9% were women and mean CHA2DS2-VASc score was 3.3 (Table 1). The proportion of patients treated with warfarin was higher in patients undergoing surgical valve intervention whereas NOAC was more commonly prescribed to patients treated with TAVI. Rates of composite CV events and major bleeding was similar between patients treated with NOAC versus warfarin. No OAC treatment versus warfarin was associated with higher rate of composite CV event, but with no difference with regard to major bleeding (Table 1). Conclusion: A large proportion of patients with AF undergoing valvular intervention was not treated with OAC despite having a high CHA2DS2-VASc score. Also, patients on no OAC versus warfarin had a higher risk of i CV events in the early phase after valvular intervention. The efficacy and safety of NOAC was similar compared to warfarin during the first 3 months after intervention. Treatment with OAC in patients with AF, irrespective of NOAC or warfarin, was associated with improved clinical outcome early after valve intervention. Funding Acknowledgement: Type of funding sources: None.